2016
DOI: 10.1111/jch.12860
|View full text |Cite
|
Sign up to set email alerts
|

Add‐On Use of Eplerenone Is Effective for Lowering Home and Ambulatory Blood Pressure in Drug‐Resistant Hypertension

Abstract: 2The authors aimed to investigate the blood pressure (BP)-lowering ability of eplerenone in drug-resistant hypertensive patients. A total of 57 drug-resistant hypertensive patients whose home BP was ≥135/85 mm Hg were investigated. The patients were randomized to either an eplerenone group or a control group and followed for 12 weeks. The efficacy was evaluated by clinic, home, and ambulatory BP monitoring. Urinary albumin, pulse wave velocity, and flowmediated vasodilation (FMD) were also evaluated. Home morn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
2
9
0
1
Order By: Relevance
“…The study by Eguchi and colleagues was able to demonstrate that eplerenone was more effective than placebo in patients with TRH, especially regarding reduction of home and ambulatory awake BP. 25 In addition to the BP reduction, this study also demonstrated an improvement in flowmediated vasodilation. 25 Similarly, in a prospective, randomized study Abbreviations: PWV, pulse wave velocity; SBP, systolic blood pressure.…”
Section: Study Limitationssupporting
confidence: 58%
See 2 more Smart Citations
“…The study by Eguchi and colleagues was able to demonstrate that eplerenone was more effective than placebo in patients with TRH, especially regarding reduction of home and ambulatory awake BP. 25 In addition to the BP reduction, this study also demonstrated an improvement in flowmediated vasodilation. 25 Similarly, in a prospective, randomized study Abbreviations: PWV, pulse wave velocity; SBP, systolic blood pressure.…”
Section: Study Limitationssupporting
confidence: 58%
“…25 In addition to the BP reduction, this study also demonstrated an improvement in flowmediated vasodilation. 25 Similarly, in a prospective, randomized study Abbreviations: PWV, pulse wave velocity; SBP, systolic blood pressure.…”
Section: Study Limitationssupporting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, aldosterone, which exerts its activity in adipocytes, is involved in abnormal production/secretion of adipocytokines by adipocytes [21] and contributes to increases in oxidative stress [22] and decreases insulin sensitivity in adipose tissue [23, 24]. Eplerenone is thought to suppress the adverse effects of aldosterone in in various organs including the endothelium by inhibiting aldosterone activity through binding to MRs [25]; thus, eplerenone is a pharmacologically promising drug to prevent end organ damage induced by aldosterone.…”
Section: Discussionmentioning
confidence: 99%
“…Согласно результатам другого метаанализа, посвященного оценке возможностей монотерапии эплереноном при лечении пациентов с первичной АГ ( [26]. Снижение АД в группе эплеренона было наиболее выраженным для амбулаторного САД, ДАД после пробуждения и 24-часового ДАД.…”
Section: огляд / Reviewunclassified